Designing a Quantitative Model for the Development of Sports for Children with Special Needs in Iran - Chegini , Abolfazl; Jamshidi, Arefeh; Tavakoli , Maryam (Psychological Research in Individuals with Exceptional Needs, 2026)
The present study aimed to design a quantitative model for the development of sports for children with special needs in Iran. In terms of purpose, the study was applied-developmental, and methodologically, it employed a descriptive-survey design. The questionnaire was developed based on the components and indicators extracted in relation to the development of sports for children with special needs. Following data collection, the proposed model was examined, tested, and validated using quantitative data. Finally, the final model and the magnitude of the effect of each factor on the development of sports for children with special needs in Iran were presented. The researcher-made questionnaire was distributed among 400 managers, experts, coaches, physical education teachers, special education specialists, rehabilitation experts, and faculty members, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM). Confirmatory factor analysis and structural equation modeling were used to examine and validate the model for the development of sports for children with special needs in Iran. Quantitative data were analyzed using SPSS version 27 and SmartPLS version 3. SPSS was used for descriptive analyses and preliminary data screening, whereas SmartPLS was employed for confirmatory factor analysis, assessment of construct validity and reliability, and validation of the final research model. The quantitative findings indicated that causal conditions had a positive and significant effect on the central phenomenon (path coefficient = 0.96; t = 160.89). Moreover, the central phenomenon (path coefficient = 0.47; t = 33.51), contextual conditions (path coefficient = 0.51; t = 40.47), and intervening conditions (path coefficient = 0.53; t = 47.12) had positive and significant effects on strategies. The effect of strategies on the outcomes of sports development for children with special needs was also positive and significant (path coefficient = 0.97; t = 167.31). The coefficients of determination for the central phenomenon, strategies, and outcomes were 0.928, 0.709, and 0.943, respectively, and the overall model goodness-of-fit index was 0.781. Overall, the research model demonstrated satisfactory explanatory power and goodness of fit and can provide a systematic framework for policymaking and planning for the development of sports for children with special needs in Iran.